Pengembangan Potensi Wisata di Kota Banda Aceh Dengan Analisa SWOT - Dewi Mulyati; Khairiadi Khairiadi; Syaifuddin Yana; Ikramullah Zein (Fakultas Teknik, 2018)
Banda Aceh is a city as well as the capital of Aceh Province that has many potentials, both in industry, fishery, history, tourism and others. One area that has the potential to be developed is the field of tourism, because the field of tourism is one source of local revenue. This research was conducted at the Department of Culture and Tourism of Aceh in 20017. The objectives of the research formulate the development strategy of Banda Aceh tourism object through SWOT approach. The results of the analysis obtained are: maintaining and improving the quality of tourist attractions, coordination with the government (related departments) and the community in the development of tourism object, utilizing the support of pemko and the community to improve the quality of tourist attractions, cooperate with special business in the field of marketing, improve the quality of human resources and multiply the supporting facilities oftourism